Optimization and characterization of graphene nanocomposites for glucose biosensors - Arris, Farrah Aida (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Continuous improvement of biosensor performance aims to improve sensitivity, as well as to allow for advancement in non-invasive, and relatively inexpensive technology that can fulfilled the increasing needs of targeted users. Most glucose sensors in the market use blood sample to test glucose level, which is not pain-free as the method requires finger pricking for blood sampling. In order to improve the performance of an electrochemical glucose biosensor that is able to detect glucose concentration in unstimulated mixed saliva in the range of 0.02 to 0.4 mM, selection of nanomaterials and methods of depositing the nanomaterials onto transducer surface were studied to select the optimized deposition conditions using immobilized glucose oxidase as model enzyme. One of the promising nanomaterials as transducer material is graphene owing to its excellent electrical properties and existence of functional groups for antibody immobilization. In this study, electrochemical characterization of graphene-based nanocomposites as transducer material for highly sensitive biosensors was performed. Parameters that were varied include graphene oxide (GO) concentration, amount of gold nanoparticles (AuNPs), addition of Nafion as a binder for enhancing electrical conductivity of the transducer layer, and methods of nanomaterials deposition onto glassy carbon electrode (GCE). The GCE-modified with nanocomposites transducer layers were fabricated via a simple two-step drop-cast and subsequent electrochemical reduction. Cyclic voltammetry (CV) was used to characterize the redox capability of the transducer layer. Electrochemical deposition of ultra highly concentrated single-layer graphene oxide (UHC GO) suspension with a concentration of 6.2 mg/ml gave higher anodic peak current, Ipa, after electrochemical reduction when compared to most peak currents reported in the literature for a 3-mm inner-diameter electrode. Furthermore, UHC rGO:AuNPs in a 2:1 ratio followed by electrochemical reduction resulted in even higher Ipa whereas adding UHC rGO:Nafion in 4:1 ratio gave promising results for prolonged shelf-life of the biosensor. Hence, UHC rGO-AuNPs-Nafion as nanocomposite is an excellent precursor for the development of a redox-active transducer that results in highly sensitive biosensors. The newly-fabricated GCE/UHC rGO-AuNPs-Nafion-GOx with ratio of 2:1:1:1 demonstrated a sensitivity of 5.6 μA.mM-1, response time of ~6 s, and a linear range of 0.2 to 0.7 mM, which demonstrated a promising precursor for enabling saliva as analyte for the development of non-invasive glucose biosensors.